Cover, Editorial Team, Table of Contents - Hanifa, Hana (Proceeding ICMA-SURE; Proceeding The 5th International Conference on Multidisciplinary Approaches for Sustainable Rural Development, 2023)
Publish Articles presented at ICMASURE 2023